基于混合遗传算法的偏曲轴少齿差行星减速机构优化设计 - 冯和平; 王丽敏; 计小辈 (Jixie chuandong)
For solving constrain optimization problems,a mixed genetic algorithm is introduced,and the planeary gear reducer of small tooth difference with biasing crank shaft.The optimization result compares with that of the traditional optimization,and feasibility and validity of the algorithm are illustrated.